2013
DOI: 10.2166/ws.2013.013
|View full text |Cite
|
Sign up to set email alerts
|

Water consumption in public schools for the city of Bologna, Italy

Abstract: For most buildings considered to be of a public non-residential type there are insufficient published data to establish and compare the theoretical standards with actual consumption data. Therefore, water consumption per user in non-residential buildings is still a very complicated issue for engineers and designers involved in analysing water demand and water management. This is why linking water consumption and school occupancy is the goal of this paper, trying to set the basis for further design, conservatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Regarding the school typology and age group of students, the per capita water consumption indicator ranged from 27 to 67 liters per student per day in early childhood education and nursery schools (Farina et al, 2013;Sanjuan-Delmás et al, 2016). In primary and secondary schools, values between 2 to 78 liters per student per day were found (Cheng;Hong, 2004;Farina et al, 2013;Antunes;Ghisi, 2019). While in high and technical schools, the indicator values ranged from 9 to 22 liters per student per day (Nunes et al, 2019;Antunes;Ghisi, 2019).…”
Section: Critical Analysis Of the Water Management Indicators Propose...mentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the school typology and age group of students, the per capita water consumption indicator ranged from 27 to 67 liters per student per day in early childhood education and nursery schools (Farina et al, 2013;Sanjuan-Delmás et al, 2016). In primary and secondary schools, values between 2 to 78 liters per student per day were found (Cheng;Hong, 2004;Farina et al, 2013;Antunes;Ghisi, 2019). While in high and technical schools, the indicator values ranged from 9 to 22 liters per student per day (Nunes et al, 2019;Antunes;Ghisi, 2019).…”
Section: Critical Analysis Of the Water Management Indicators Propose...mentioning
confidence: 99%
“…In the USA, approximately 6% of total water use in commercial and institutional facilities takes place in educational facilities, such as schools, universities, museums, and libraries (Dziegielewski et al, 2000). In a study conducted in the city of Bologna, Italy, Farina et al (2013) estimated a water demand equal to 48.8 L per pre-school student per day and 18.7 L per elementary/secondary school student per day. Although there is a variation in the typology of buildings, Nunes et al (2019) found a reference range for the consume indicator equal to 13.0 ± 2.0 L/ per student per day for water considering the set of all school typologies in the city of Recife, Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation